Numerical simulation of biodiesel production using waste cooking oil - Mohiuddin, A. K. M.; Adeyemi, Nabeel A. (2013)
The goal of this work was to carry out transesterification using computational fluid dynamics (CFD) method and obtain yield comparable to experimental values. First of all, the single–phase flow field was simulated and compared with experimental data obtained by means of particle image velocimetry (PIV) measurements. The velocities calculated from the RSM approach agreed quite well with those from PIV. The CFD simulations of biodiesel production were performed using the Reynolds stress model (RSM) coupled with the eddy dissipation model (EDM). CFD analysis of biodiesel yield compared fairly well with the experimental results available.